The Influence of Transformational Leadership Style, Human Resources Competency Towards Implementation Performance Based Budgeting and Organization Culture - Desi Kirana Putri (Perkumpulan Praktisi Akuntansi Indonesia, 2021)
This research has the aim of recognizing and knowing the influence of transformational leadership style, the competence of human resources on the implementation of performance-based budgeting with organizational culture. This research was conducted using the quantitative method. Hypothetical testing in the study used SPSS v.23 analysis. The results of the research tested using SPSS gave results that the transformational leadership style and competence of human resources affected the implementation of performance-based budgets. However, according to organizational culture, the transformational leadership style and competence of human resources have no effect on the implementation of performance-based budgets.